US GOVERNMENT INFORMATION SECURITY POLICY DEVELOPMENT PROCESS - Aliyev Olimbek Aybekovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
From the second half of the last century, a period of radical change in the field of information security began in the United States. Since then, serious efforts have been made in the field of state computer and information security. In particular, legal-regulatory documents and legislation related to the field have been improved. The article discusses and analyzes the same issues